Optimization of interval formulas for approximate integration of set-valued functions monotone with respect to inclusion - Babenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The best interval quadrature formula is obtained for the class of convex set-valued functions defined on the segment [0, 1] and monotone with respect to inclusion.